The debt management conditions of local government units in Poland - Tobera, Paweł (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
Operating in Poland since 1999 the three-tier administrative division of the country (communes, districts and provinces) has helped to increase the financial independence of these units. The main objective of introducing Poland with a system of country division into individual local government units was essentially the pursuit of efficient, and therefore, the effective functioning of the state in all spheres of public activity. This primarily involved the establishment of a range of criteria, rights and obligations which different parties have accepted. Due to the significant amount of a wide range of tasks that result from the functioning of local government, it is difficult now to imagine the existence of the state without taking into account such a segmentation of these entities. Local government units, which are included in the local government sector due to the large range of tasks assigned to them, play an extremely important role when it comes to the management of public funds. This is related to the broader decentralization of public tasks and also to some extent of autonomy in shaping their own fiscal policies. Since the introduction of local government reform a large number of operators in the sector are facing a growing debt problem which is also reflected in the increase of the public debt level. In the main extent this is the result of the aforementioned decentralization of tasks, in other words, the transfer of a substantial part of the state’s obligations related to the functioning of the country to the level of local government (Marchewka and Bartkowiak, 2012). Due to the limited amount of funds it significantly contributes to reducing opportunities for the entity of local government, and as a consequence it forces local government authorities to use debt instruments such as credits, loans and issuance of debt securities. However, the debt results from the lack of stable budgetary policy in the sense of its possibilities. Sometimes, from the moment of creation of the budget for the next year we can see some kind of lack of vision and planning to continue the development of the unit in the future, which could contribute to stabilizing its finances. You could say that for the governing bodies of local government units ‘it’s all about the here and now’. A key element contributing to the debt growth of the local government sector over the last few years was also the possibility to use funds from the European Union and other non-refundable external funds. Unfortunately, this is conditioned by the necessity of bringing their own contribution, which in turn imposes the use of debt instruments. Because of the fact that the debt, which is generated by local government, affects the growth of the state debt level and involves a risk of exceeding the legally adopted restrictions in this area, it is also connected to the so-called safety thresholds. The problem of local government debt is mainly linked with all activities relating to the analysis of the debt. This man itself through the introduction of appropriate indicators that determine the situations enabling the occurrence of debt, as well as the designation of mechanisms for debt monitoring. In Poland so far lacked strict financial rules, which would help to gradually reduce the borrowing of local government entities. Constantly increasing n the indebtedness of local governments sector entities contributed significantly to the increase in debt at the national level. This was particularly relevant when it cames to managing public finance sector debt. Introduced regulations in Poland are expected to contribute to a gradual reduction of the debt of local government units. The following article attempts to bring the issues of control and reduction of local government debt in connection to new restrictions implemented at the Polish local government level.